The effect of long‐term left ventricular assist device support on myocardial sympathetic activity in patients with non‐ischaemic dilated cardiomyopathy. (September 2013) - George, Robert S.; Birks, Emma J.; Cheetham, Andrew; Webb, Carole; Smolenski, Ryszad T.; Khaghani, Asghar; Yacoub, Magdi H.; Kelion, Andrew
<x xml:space="preserve">Abstract</x> Aims Dilated cardiomyopathy (DCM) patients have abundant levels of norepinephrine secondary to failure of the norepinephrine transporter uptake mechanism. Little is known about the effects of an LV assist device (LVAD) on cardiac sympathetic innervations and norepinephrine transporter dysfunction. This study examines the effects of continuous‐flow HeartMate II LVAD on cardiac sympathetic innervations using [123I]metaiodobenzylguanidine ([123I]MIBG) nuclear imaging. Methods and results After injecting 431 ± 21 MBq of [123I]MIBG, planar scintigraphy was performed at 15 min and 4 h in 14 consecutive non‐diabetic non‐ischaemic DCM patients. Scans were executed early post‐LVAD implantation (T1) and prior to either device explantation for myocardial recovery or transplant listing (T2). [123I]MIBG measured parameters included early and delayed heart–mediastinum (H/M) ratios and washout rate (W/O). Catecholamine levels were measured using liquid chromatography–mass spectrometry. Following 208.4 ± 85.5 days of LVAD support, both early and delayed H/M ratios increased by 42.1% (P < 0.001) and 54.7% (P < 0.001), respectively. The W/O rate decreased by 46% (P = 0.003). Plasma norepinephrine, epinephrine, and dopamine decreased significantly in correlation with [123I]MIBG parameters. Ten patients had recovered and had their device explanted as they had demonstrated a higher percentage change in delayed H/M ratio, W/O rate, and norepinephrine levels. Linear regression analysis revealed a strong correlation between percentage changes in both norepinephrine and epinephrine and myocardial recovery. Conclusion Combination therapy with LVAD and drug resulted in enhancement of [123I]MIBG uptake in DCM patients.